Analysis of the Influence of Local Tax Revenue, Regional Retribution and Results of Separate Regional Wealth Management on Regional Original Revenue (PAD) of North Sumatra Regency/City - M. Iqbal Anugerah Berutu; Annathasia Puji Erasashanti (Indonesian Journal of Economic & Management Sciences, 2023)
Analysis is the main objective of research on the influence of Regional Taxes, Regional Levies and Results of Separated Wealth Management on Regional Original Income of the Regency/City of North Sumatra Province. This study uses quantitative research using the second type of data. The population used in this study is called the report. Realization of District/City Regional Revenue of North Sumatra Province in 2018-2020. The sample used is the Report on the Realization of Regional Tax Revenue, Regional Penalties and the Impact of Regional Wealth Management of Separated Regencies/Cities in North Sumatra Province in 2018-2020. Multiple linear regression using SPSS Version 22 is the analytical method used. The research findings show that local levies and taxes have a positive and sizeable impact on regional own-source revenues. However, Regional Original Income is not significantly affected by the management of Regional Wealth